Starry messenger a book depicting the life of a famous scientist, mathematician, astronomer, philosopher, physicist, Galileo Galilei - Sis, Peter 1949- (New York Farrar Straus Giroux, 2000)
Describes the life and work of the courageous man who changed the way people saw the galaxy, by offering objective evidence that the earth was not the fixed center of the universe.
"A Caldecott honor book."
"An ALA notable book."
Keywords: Galilei, Galileo -- 1564-1642 -- Juvenile literature; Astronomers -- Italy -- Biography -- Juvenile literature; Scientists -- Italy -- Biography -- Juvenile literature